“TÉCNICAS GRAFOPLÁSTICAS PARA EL DESARROLLO MOTRIZ DE LA ESCRITURA EN LOS ESTUDIANTES DEL TERCER AÑO PARALELO “D” DE LA UNIDAD EDUCATIVA JUAN DE VELASCO SEDE JUAN BERNARDO DE LEÓN PARA EL PERÍODO LECTIVO 2017-2018” - Santillán Paucar, Rosa Elena (2019)
The main objective of this research is to determine some Graphoplastic techniques for motor development or writing at Unidad Educativa Juan de Velasco, venue Juan Bernardo de León Juan de Velasco, during 2017-2018. Forty children participated in the research. It is a non-experimental investigation since there was neither manipulation nor control of any of the two variables. In addition, the type and design of the research are descriptive and in situ. In fact, it allows obtaining data and collect all necessary information for preparing the research project in order to respond to any situation or problem. The investigation technique is observation because the venue was visited directly to later conduct its respective analysis. For data collection from participants, observation sheet was the most appropriate instrument. It allowed fulfilling the proposed objective during the realization of this research. It can be concluded that children show to with motor development for performing writing.